Analisis Penentuan Margin Pada Pembiayaan Murabahah Di Baitul Maal Wa Tamwil (BMT) El-Hidayah Khoiru Ummah - Wahida, Rahma; Rabby, Annisa Rahmani; Yulvyanti, Vera Andela; Aprilia, Ayu Vadia; Carmidah, Carmidah (Maisyatuna, 2024)
Sharia financial institutions are institutions that provide a buying and selling system (murabahah) by trying to avoid the interest system, because bank interest is considered usury and Allah SWT forbids all transactions that contain elements of usury. The aim of this research is to find out how the margin is determined in murabahah financing. In this case the researcher used interview and observation methods. Determining the margin distribution at BMT El-Hidayah Khoiru Ummah is carried out using three methods, including: the sliding profit margin method, the average profit margin method and the flat profit margin method. After conducting research, it is known that murabahah financing on BMT is in accordance with PSAK 102 and the MUI Fatwa.